2006
DOI: 10.1037/0096-1523.32.4.986
|View full text |Cite
|
Sign up to set email alerts
|

The beat goes on: Rhythmic modulation of cortical potentials by imagined tapping.

Abstract: A frequency analysis was used to tag cortical activity from imagined rhythmic movements. Participants synchronized overt and imagined taps with brief visual stimuli presented at a constant rate, alternating between left and right index fingers. Brain potentials were recorded from across the scalp and topographic maps made of their power at the alternation frequency between left and right taps. Two prominent power foci occurred in each hemisphere for both overt and imagined taps, one over sensorimotor cortex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Observation-related neural activity in the absence of overt motor practice appears sufficient to result in implicit motor learning (15,16). It has been shown that imagined finger movements lead to cortical activity that in part resembles the activity seen during real movements (17). An intriguing possibility is that the mapping of observed movements onto one's own neural system for generating movement activates the so-called 'mirror neuron system', a system thought to be equivalent to the mirror neurons described in animals (18).…”
Section: Discussionmentioning
confidence: 99%
“…Observation-related neural activity in the absence of overt motor practice appears sufficient to result in implicit motor learning (15,16). It has been shown that imagined finger movements lead to cortical activity that in part resembles the activity seen during real movements (17). An intriguing possibility is that the mapping of observed movements onto one's own neural system for generating movement activates the so-called 'mirror neuron system', a system thought to be equivalent to the mirror neurons described in animals (18).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we found a trend toward a negative-going shift even before rule-based omissions themselves. We speculate that this may correspond to an internal preparation or simulation process, which occurs even when action execution is omitted (Osman, Albert, Ridderinkhof, Band, & van der Molen, 2006) -indeed several fMRI studies confirm that primary motor cortex is often activated during simulated or imagined action (Lacourse, Orr, Cramer, & Cohen, 2005;Gerardin et al, 2000;Lotze et al, 1999). Interestingly, this component was not present for voluntary decisions to omit.…”
Section: Competition Between Action and Omissionmentioning
confidence: 99%
“…In addition, an ERP is elicited around 100 ms after movement onset, whose source is located in the primary somatosensory cortex, suggesting that this potential reflects tactile and somatosensory feedback. In the frequency domain, the repetitive movements elicit SS-EPs at frequencies corresponding to the frequency of the periodic movement [52][53][54]57,58]. This approach appears to be a powerful way to increase the signal-to-noise ratio with reduced testing duration.…”
Section: Neural Entrainment Underlying Sensorimotor Synchronization Tmentioning
confidence: 99%